A hydrogen-sensitive color-changing film based on nanomaterials and a preparation method thereof

Hydrogen-sensitive color change with high sensitivity and short response time was prepared by using hydrothermal reaction process of sodium tungstate, sodium metavanadate and carbon nanotubes in hydrogen-sensitive color change films, combined with vinyl silicone rubber and silane coupling agents. Thin film solves the problems of long response time and poor mechanical properties of hydrogen in the prior art.

CN118725375BActive Publication Date: 2024-12-31SUZHOU PAN HYDROGEN NEW MATERIAL TECH CO LTD +1
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411207434.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-08-30
Publication Date
2024-12-31
Estimated Expiration
2044-08-30

AI Technical Summary

Technical Problem

The existing hydrogen-sensitive discolored films have a long response time to hydrogen and have average mechanical properties, which cannot meet the needs of high sensitivity and rapid response.

Method used

Sodium tungstate, sodium metavanadate and carbon nanotubes are used to carry out hydrothermal reaction in an acidic environment to form a V-doped WO3-carbon nanotube composite material, combined with vinyl silicone rubber and silane coupling agent, and through calcining and molding process Prepare hydrogen-sensitive discoloration films to improve their sensitivity and mechanical properties.

Benefits of technology

The prepared hydrogen-sensitive discoloration film has high sensitivity, short response time, excellent dispersion and compatibility, which improves the selectivity and adsorption ability of hydrogen, and enhances mechanical properties and stability.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention relates to the technical field of hydrogen-sensitive materials, and discloses a hydrogen-sensitive color-changing film based on nanomaterials and a preparation method thereof. Sodium tungstate is used as a tungsten source and sodium metavanadate is used as a vanadium source. In an acidic environment, n-propanol is used as an organic inducing agent, and carbon nanotubes act together to produce a hydrothermal reaction to obtain a precursor; the precursor is calcined in an argon atmosphere to obtain a V-doped WO3-carbon nanotube composite material having a unique nanostructure and a higher specific surface area; the V-doped WO3-carbon nanotube composite material is used as a hydrogen-sensitive material, and is stirred and mixed with vinyl silicone rubber and a dispersant, and after refining and molding, a hydrogen-sensitive color-changing film based on nanomaterials is obtained. V-doped WO3 has a high specific surface area and abundant reaction sites, which can increase the adsorption capacity of hydrogen and improve the selectivity of hydrogen. Carbon nanotubes have excellent mechanical properties, which effectively improve the mechanical properties of the film. The prepared hydrogen-sensitive color-changing film has the characteristics of high sensitivity and short response time.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of hydrogen-sensitive materials, and in particular to a hydrogen-sensitive color-changing film based on nanomaterials and a preparation method thereof. Background Art

[0002] Energy and environmental issues, as the two major themes of the development of the world today, have received more and more attention. With the over-exploitation of fossil energy, more and more problems are faced. The depletion of secondary energy and the pollution caused by the use of secondary energy have become difficult problems that need to be solved. Hydrogen energy has the advantages of high efficiency, cleanliness, environmental protection, and renewability. It has great practical value. The development and use of hydrogen energy is of great significance to cope with the energy crisis and the pollution problems caused by the use of secondary energy, and has received widespread attention. However, hydrogen is also flammable and explosive, and there are certain safety hazards in the preparation, storage, transportation and use. Since hydrogen is colorless, odorless and has strong permeability, in order to safely use hydrogen energy, it is necessary to develop and use hydrogen-sensitive materials with high sensitivity and stable working performance to detect hydrogen leaks.

[0003] Chinese patent CN114180850A provides a vanadium-doped crystalline tungsten trioxide electrochromic film and a preparation method thereof. The molar ratio of vanadium atoms to tungsten atoms in the vanadium-doped crystalline tungsten trioxide electrochromic film is (0.01-0.1). The preparation process is as follows: 1cm×4cm ITO glass is ultrasonically cleaned by acetone, ethanol, and deionized water, respectively, and placed in an oven for drying; sodium metavanadate and sodium tungstate are weighed, dissolved in deionized water, 30% hydrogen peroxide solution is added, and an appropriate amount of sulfuric acid solution is added to adjust the pH; a three-electrode system is used for deposition to obtain a tungsten oxide film; and the film is calcined in a muffle furnace to obtain a crystalline tungsten oxide film. The preparation method is simple to operate, low in cost, and does not require the addition of a template agent. The prepared film has uniform pore structure, excellent electrochromic performance, and good cycle stability. However, the film has a long response time and average sensitivity. Summary of the invention

[0004] In order to solve the above technical problems, the present invention provides a hydrogen-sensitive color-changing film based on nanomaterials and a preparation method thereof, which solves the problem that the hydrogen-sensitive color-changing film has a long response time to hydrogen and general mechanics.

[0005] In order to achieve the above object, the present invention discloses a method for preparing a hydrogen-sensitive color-changing film based on nanomaterials, comprising the following steps:

[0006] Step 1: Sodium tungstate is dissolved in deionized water, mixed evenly, sodium metavanadate is added, hydrochloric acid aqueous solution is used to adjust the pH to 1.6-2.4, n-propanol is added, stirred and mixed, and carbon nanotube dispersion is added to obtain a mixed solution, and the mixed solution is transferred to a reactor for hydrothermal reaction. After the reaction is completed, it is cooled and centrifuged at a rate of 6000 r / min for 6 minutes. The solid product obtained by centrifugation is washed with deionized water and anhydrous ethanol until neutral, and then vacuum dried in a vacuum drying oven at 60°C for 12 hours to obtain V-doped WO 3 -Carbon nanotube composite material precursor;

[0007] Step 2: Doping V into WO 3 -The carbon nanotube composite material precursor is placed in a muffle furnace and calcined in an inert gas atmosphere. After the calcination, it is cooled to room temperature in an inert gas atmosphere, ground and sieved to obtain V-doped WO 3 - Carbon nanotube composites;

[0008] Step 3: Doping V into WO 3 -The carbon nanotube composite material, vinyl silicone rubber and dispersant are put into a mixer and stirred and mixed evenly, then refined in an open mill, and then formed in a molding machine to obtain a hydrogen-sensitive color-changing film based on nanomaterials.

[0009] Preferably, in step 1, the mass ratio of sodium tungstate, deionized water, sodium metavanadate, n-propanol and carbon nanotube dispersion is 100:130-150:0.2-0.7:1-3:18-30.

[0010] Preferably, in step 1, the temperature of the hydrothermal reaction is 150-180° C., and the time of the hydrothermal reaction is 8-12 h.

[0011] Preferably, in step 1, the aqueous hydrochloric acid solution is an aqueous hydrochloric acid solution with a concentration of 0.3 mol / L.

[0012] Preferably, in the step 1, the concentration of the carbon nanotube dispersion is 50 g / L, and the carbon nanotube dispersion is an aqueous solution of carbon nanotubes after acidification;

[0013] The steps for preparing the acid-treated carbon nanotubes are as follows:

[0014] The multi-walled carbon nanotubes were added into a 37wt% hydrochloric acid solution in a mass ratio of 1:5. The mixture was stirred for 1 hour and then ultrasonically dispersed at a temperature of 70-80°C for 3-4 hours. The mixture was filtered and washed with deionizer until neutral. The mixture was vacuum dried at 60°C for 6 hours to obtain the acidified carbon nanotubes.

[0015] Preferably, in the step 2, the calcination temperature is 450-520° C., and the calcination time is 2-3 hours.

[0016] Preferably, in step 2, the inert gas includes argon.

[0017] Preferably, in step 2, V doped WO 3 -The average particle size of the carbon nanotube composite material is less than 0.1 μm.

[0018] Preferably, in step 3, V doped WO 3 -The mass ratio of carbon nanotube composite material, vinyl silicone rubber and dispersant is 18-25:100:1-3.

[0019] Preferably, in step three, the dispersant includes a silane coupling agent.

[0020] Preferably, in step three, the silane coupling agent includes a vinyl silane coupling agent.

[0021] Furthermore, the vinyl silane coupling agent is γ-(methacryloyloxy)propyltrimethoxysilane.

[0022] Preferably, in step 3, the stirring and mixing speed is 240-300 r / min; the refining temperature is 160-200° C., and the refining time is 12-15 min.

[0023] Preferably, the hydrogen-sensitive color-changing film based on nanomaterials is prepared by the method for preparing the hydrogen-sensitive color-changing film based on nanomaterials.

[0024] Compared with the prior art, the present invention has the following beneficial effects:

[0025] In the present invention, sodium tungstate is used as a tungsten source and sodium metavanadate is used as a vanadium source. In an acidic environment, n-propanol is used as an organic inducer. Under hydrothermal conditions, the carbon nanotubes react with each other to obtain V-doped WO. 3 -Carbon nanotube composite precursor, V-doped WO 3 -The carbon nanotube composite precursor is calcined in an inert gas atmosphere to obtain V-doped WO with a unique nanostructure and a higher specific surface area. 3 -Carbon nanotube composites; V-doped WO 3 - Carbon nanotube composite material is used as hydrogen-sensitive material, mixed with vinyl silicone rubber and dispersant vinyl silane coupling agent, and then smelted and formed to obtain a hydrogen-sensitive color-changing film based on nanomaterials; among them, the dispersant vinyl silane coupling agent can effectively improve the V-doped WO 3-The dispersion of carbon nanotube composite materials, reacting with vinyl silicone rubber, the prepared film has excellent dispersion and compatibility, and uniform performance.

[0026] The carbon nanotubes in the present invention have a high specific surface area and abundant reaction sites, which can effectively improve the sensitivity and response speed of the composite material, and also have the characteristics of high conductivity and chemical stability. 3 With high electron density and oxygen mobility, it can effectively improve the conductivity and hydrogen sensitivity of the composite material. 3 In the case of V, it exists in the +5 valence state and can replace WO 3 The tungsten atoms in the WO generate holes, which enhance the 3 At the same time, since the radius of vanadium is similar to that of tungsten, it will not destroy WO 3 Crystal structure of V-doped WO 3 With high specific surface area and abundant reaction sites, V-doped WO 3 It can also increase the adsorption capacity of hydrogen and improve the selectivity of hydrogen, and the selectivity is good. The prepared hydrogen-sensitive color-changing film has the characteristics of high sensitivity and short response time.

[0027] In the present invention, WO 3 After reacting with hydrogen, the hydrogen molecules adsorbed on the surface of the hydrogen-sensitive color-changing film are decomposed into hydrogen atoms under the action of the catalytic layer. The hydrogen atoms diffuse into the film along the pore surface of the film. During the diffusion process, two hydrogen atoms react with WO 3 One oxygen atom at the grain boundary combines to form water, thus forming water in WO 3 Oxygen vacancies are formed in the grains, and the oxygen vacancies diffuse into the grains to form color centers, which causes the film to change color and generate a blue bronze structure: 0.5xH 2 +WO 3 →HxWO 4 , the electron in W 6+ With W 5+ Due to the transition between the two, the color of the hydrogen-sensitive color-changing film will change from transparent to blue after the reaction.

[0028] The carbon nanotubes in the present invention have the advantages of small size, large specific surface area, strong adsorption capacity, high conductivity and low operating temperature. Since the high surface area carbon nanotubes can adsorb a large amount of gas, the sensitivity and response time to hydrogen are effectively improved. 3 Grown on carbon nanotubes, the growth density is high, the specific surface area of ​​the material is increased, it has good hydrogen response ability, and the color change time is fast. At the same time, carbon nanotubes have excellent mechanical properties, and vinyl silicone rubber has excellent elasticity and mechanical properties, which effectively improves the mechanical properties of the film. At the same time, vinyl silicone rubber also protects hydrogen-sensitive materials and improves the stability, safety and service life of the film. DETAILED DESCRIPTION

[0029] The technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0030] Example 1

[0031] A method for preparing a hydrogen-sensitive color-changing film based on nanomaterials comprises the following steps:

[0032] Step 1: dissolve sodium tungstate in deionized water, mix well, add sodium metavanadate, adjust the pH to 1.6 with 0.3 mol / L hydrochloric acid aqueous solution, add n-propanol, stir and mix, add 50 g / L carbon nanotube dispersion to obtain a mixed solution, wherein the mixed solution is obtained by mixing sodium tungstate, deionized water, sodium metavanadate, n-propanol and carbon nanotube dispersion in a mass ratio of 100:130:0.2:1:18, transfer the mixed solution to a reactor, and perform a hydrothermal reaction at a temperature of 150°C for 12 hours. After the reaction is completed, cool and centrifuge at a centrifugal speed of 6000 r / min for 6 minutes. The solid product obtained by centrifugation is washed with deionized water and anhydrous ethanol until neutral, and then vacuum dried in a vacuum drying oven at 60°C for 12 hours to obtain V-doped WO 3 -Carbon nanotube composite material precursor;

[0033] The carbon nanotube dispersion is an aqueous solution of carbon nanotubes after acidification, and the preparation steps of the carbon nanotubes after acidification are as follows: adding multi-walled carbon nanotubes to a 37wt% hydrochloric acid solution, the mass ratio of the multi-walled carbon nanotubes to the 37wt% hydrochloric acid solution is 1:5, stirring for 1h, and then ultrasonically dispersing, the ultrasonic dispersion temperature is 70°C, the ultrasonic dispersion time is 4h, suction filtering, washing with deionized water to neutrality, and vacuum drying at 60°C for 6h to obtain the carbon nanotubes after acidification;

[0034] Step 2: Doping V into WO 3 -The carbon nanotube composite material precursor was placed in a muffle furnace and calcined in an argon atmosphere at a temperature of 450°C for 3 hours. After the calcination, it was cooled to room temperature in an argon atmosphere, ground and sieved to obtain V-doped WO 3 - Carbon nanotube composite material, with an average particle size of less than 0.1 μm;

[0035] Step 3: Dope WO with V at a mass ratio of 18:100:1 3 -The carbon nanotube composite material, vinyl silicone rubber and dispersant γ-(methacryloyloxy)propyltrimethoxysilane are placed in a mixer and stirred at a speed of 240 r / min to mix evenly, and then refined in an open mill at a refining temperature of 160° C. for 15 min, and then formed in a molding machine to obtain a hydrogen-sensitive color-changing film based on nanomaterials.

[0036] Example 2

[0037] A method for preparing a hydrogen-sensitive color-changing film based on nanomaterials comprises the following steps:

[0038] Step 1: dissolve sodium tungstate in deionized water, mix well, add sodium metavanadate, adjust the pH to 2 with 0.3 mol / L hydrochloric acid aqueous solution, add n-propanol, stir and mix, add 50 g / L carbon nanotube dispersion to obtain a mixed solution, wherein the mixed solution is obtained by mixing sodium tungstate, deionized water, sodium metavanadate, n-propanol and carbon nanotube dispersion in a mass ratio of 100:138:0.4:1.8:22, transfer the mixed solution to a reactor, and undergo a hydrothermal reaction at a temperature of 160°C for 9 hours. After the reaction is completed, cool and centrifuge at a centrifugal rate of 6000 r / min for 6 minutes. The solid product obtained by centrifugation is washed with deionized water and anhydrous ethanol until neutral, and then vacuum dried in a vacuum drying oven at 60°C for 12 hours to obtain V-doped WO 3 -Carbon nanotube composite material precursor;

[0039] The carbon nanotube dispersion is an aqueous solution of carbon nanotubes after acidification, and the preparation steps of the carbon nanotubes after acidification are as follows: adding multi-walled carbon nanotubes to a 37wt% hydrochloric acid solution, the mass ratio of the multi-walled carbon nanotubes to the 37wt% hydrochloric acid solution is 1:5, stirring for 1h, and then ultrasonically dispersing, the ultrasonic dispersion temperature is 75°C, the ultrasonic dispersion time is 3.5h, filtering, washing with deionized water to neutrality, and vacuum drying at 60°C for 6h to obtain the carbon nanotubes after acidification;

[0040] Step 2: Doping V into WO 3 -The carbon nanotube composite material precursor was placed in a muffle furnace and calcined in an argon atmosphere at a temperature of 480°C for 2.5 hours. After the calcination, it was cooled to room temperature in an argon atmosphere, ground and sieved to obtain V-doped WO 3 - Carbon nanotube composite material, with an average particle size of less than 0.1 μm;

[0041] Step 3: Dope WO with V at a mass ratio of 21:100:23 -The carbon nanotube composite material, vinyl silicone rubber and dispersant γ-(methacryloyloxy)propyltrimethoxysilane are placed in a mixer and stirred at a speed of 260 r / min to mix evenly, and then refined in an open mill at a refining temperature of 175°C and a refining time of 13 min. Then, the mixture is formed in a molding machine to obtain a hydrogen-sensitive color-changing film based on nanomaterials.

[0042] Example 3

[0043] A method for preparing a hydrogen-sensitive color-changing film based on nanomaterials comprises the following steps:

[0044] Step 1: dissolve sodium tungstate in deionized water, mix well, add sodium metavanadate, adjust the pH to 2 with 0.3 mol / L hydrochloric acid aqueous solution, add n-propanol, stir and mix, add 50 g / L carbon nanotube dispersion to obtain a mixed solution, wherein the mixed solution is obtained by mixing sodium tungstate, deionized water, sodium metavanadate, n-propanol and carbon nanotube dispersion in a mass ratio of 100:145:0.6:2.5:26, transfer the mixed solution to a reactor, and perform a hydrothermal reaction at a temperature of 170°C for 10 hours. After the reaction is completed, cool and centrifuge at a centrifugal rate of 6000 r / min for 6 minutes. The solid product obtained by centrifugation is washed with deionized water and anhydrous ethanol until neutral, and then vacuum dried in a vacuum drying oven at 60°C for 12 hours to obtain V-doped WO 3 -Carbon nanotube composite material precursor;

[0045] The carbon nanotube dispersion is an aqueous solution of carbon nanotubes after acidification, and the preparation steps of the carbon nanotubes after acidification are as follows: adding multi-walled carbon nanotubes to a 37wt% hydrochloric acid solution, the mass ratio of the multi-walled carbon nanotubes to the 37wt% hydrochloric acid solution is 1:5, stirring for 1h, and then ultrasonically dispersing, the ultrasonic dispersion temperature is 75°C, the ultrasonic dispersion time is 3.5h, filtering, washing with deionized water to neutrality, and vacuum drying at 60°C for 6h to obtain the carbon nanotubes after acidification;

[0046] Step 2: Doping V into WO 3 -The carbon nanotube composite material precursor was placed in a muffle furnace and calcined in an argon atmosphere at a temperature of 500°C for 2.5 hours. After the calcination, it was cooled to room temperature in an argon atmosphere, ground and sieved to obtain V-doped WO 3 - Carbon nanotube composite material, with an average particle size of less than 0.1 μm;

[0047] Step 3: Dope WO with V at a mass ratio of 24:100:2.5 3-The carbon nanotube composite material, vinyl silicone rubber and dispersant γ-(methacryloyloxy)propyltrimethoxysilane are placed in a mixer and stirred at a speed of 280 r / min to mix evenly, and then refined in an open mill at a refining temperature of 185° C. for 14 min, and then molded in a molding machine to obtain a hydrogen-sensitive color-changing film based on nanomaterials.

[0048] Example 4

[0049] A method for preparing a hydrogen-sensitive color-changing film based on nanomaterials comprises the following steps:

[0050] Step 1: dissolve sodium tungstate in deionized water, mix well, add sodium metavanadate, adjust the pH to 2.4 with 0.3 mol / L hydrochloric acid aqueous solution, add n-propanol, stir and mix, add 50 g / L carbon nanotube dispersion to obtain a mixed solution, wherein the mixed solution is obtained by mixing sodium tungstate, deionized water, sodium metavanadate, n-propanol and carbon nanotube dispersion in a mass ratio of 100:150:0.7:3:30, transfer the mixed solution to a reactor, and perform a hydrothermal reaction at a temperature of 180°C for 8 hours. After the reaction is completed, cool and centrifuge at a centrifugal speed of 6000 r / min for 6 minutes. The solid product obtained by centrifugation is washed with deionized water and anhydrous ethanol until neutral, and then vacuum dried in a vacuum drying oven at 60°C for 12 hours to obtain V-doped WO 3 -Carbon nanotube composite material precursor;

[0051] The carbon nanotube dispersion is an aqueous solution of carbon nanotubes after acidification, and the preparation steps of the carbon nanotubes after acidification are as follows: adding multi-walled carbon nanotubes to a 37wt% hydrochloric acid solution, the mass ratio of the multi-walled carbon nanotubes to the 37wt% hydrochloric acid solution is 1:5, stirring for 1h, and then ultrasonically dispersing, the ultrasonic dispersion temperature is 80°C, the ultrasonic dispersion time is 3h, suction filtering, washing with deionized water to neutrality, and vacuum drying at 60°C for 6h to obtain the carbon nanotubes after acidification;

[0052] Step 2: Doping V into WO 3 -The carbon nanotube composite material precursor was placed in a muffle furnace and calcined in an argon atmosphere at a temperature of 520°C for 2 hours. After the calcination, it was cooled to room temperature in an argon atmosphere, ground and sieved to obtain V-doped WO 3 - Carbon nanotube composite material, with an average particle size of less than 0.1 μm;

[0053] Step 3: Dope WO with V at a mass ratio of 25:100:3 3-The carbon nanotube composite material, vinyl silicone rubber and dispersant γ-(methacryloyloxy)propyltrimethoxysilane are placed in a mixer and stirred at a speed of 300 r / min for uniform mixing, and then refined in an open mill at a temperature of 200° C. for 12 min, and then molded in a molding machine to obtain a hydrogen-sensitive color-changing film based on nanomaterials.

[0054] Comparative Example 1

[0055] A method for preparing a hydrogen-sensitive color-changing film comprises the following steps:

[0056] Step 1: dissolve sodium tungstate in deionized water, mix well, add sodium metavanadate, adjust the pH to 2 with 0.3 mol / L hydrochloric acid aqueous solution, add n-propanol, stir and mix to obtain a mixed solution, wherein the mixed solution is obtained by mixing sodium tungstate, deionized water, sodium metavanadate and n-propanol in a mass ratio of 100:145:0.6:2.5, transfer the mixed solution to a reactor, and undergo a hydrothermal reaction at a temperature of 170°C for 10 hours. After the reaction is completed, cool and centrifuge at a rate of 6000 r / min for 6 minutes. The solid product obtained by centrifugation is washed with deionized water and anhydrous ethanol until neutral, and then vacuum dried in a vacuum drying oven at 60°C for 12 hours to obtain V-doped WO 3 Composite material precursors;

[0057] Step 2: Doping V into WO 3 The precursor was placed in a muffle furnace and calcined in an argon atmosphere at a temperature of 500°C for 2.5 hours. After the calcination, it was cooled to room temperature in an argon atmosphere, ground and sieved to obtain V-doped WO. 3 , the average particle size is less than 0.1 μm;

[0058] Step 3: Dope WO with V at a mass ratio of 24:100:2.5 3 , vinyl silicone rubber and dispersant γ-(methacryloyloxy)propyltrimethoxysilane are put into a mixer and stirred at a speed of 280r / min to mix evenly, and then refined in an open mill at a temperature of 185°C and a time of 14min. Then, they are molded in a molding machine to obtain a hydrogen-sensitive color-changing film.

[0059] Comparative Example 2

[0060] A method for preparing a hydrogen-sensitive color-changing film comprises the following steps:

[0061] Step 1: Sodium tungstate is dissolved in deionized water, mixed evenly, and the pH is adjusted to 2 with a 0.3 mol / L hydrochloric acid aqueous solution, and then n-propanol is added. After stirring and mixing, a carbon nanotube dispersion with a concentration of 50 g / L is added to obtain a mixed solution, wherein the mixed solution is obtained by mixing sodium tungstate, deionized water, n-propanol and carbon nanotube dispersion in a mass ratio of 100:145:2.5:26. The mixed solution is transferred to a reactor for hydrothermal reaction. The temperature of the hydrothermal reaction is 170°C, and the time of the hydrothermal reaction is 10 hours. After the reaction is completed, it is cooled and centrifuged. The centrifugal speed is 6000 r / min, and the centrifugal time is 6 minutes. The solid product obtained by centrifugation is washed with deionized water and anhydrous ethanol until neutral, and then vacuum dried in a vacuum drying oven at 60°C for 12 hours to obtain WO 3 -Carbon nanotube composite material precursor;

[0062] The carbon nanotube dispersion is an aqueous solution of carbon nanotubes after acidification, and the preparation steps of the carbon nanotubes after acidification are as follows: adding multi-walled carbon nanotubes to a 37wt% hydrochloric acid solution, the mass ratio of the multi-walled carbon nanotubes to the 37wt% hydrochloric acid solution is 1:5, stirring for 1h, and then ultrasonically dispersing, the ultrasonic dispersion temperature is 75°C, the ultrasonic dispersion time is 3.5h, filtering, washing with deionized water to neutrality, and vacuum drying at 60°C for 6h to obtain the carbon nanotubes after acidification;

[0063] Step 2: WO 3 -The carbon nanotube composite material precursor was placed in a muffle furnace and calcined in an argon atmosphere at a temperature of 500°C for 2.5 hours. After the calcination, it was cooled to room temperature in an argon atmosphere, ground and sieved to obtain WO 3 - Carbon nanotube composite material, with an average particle size of less than 0.1 μm;

[0064] Step 3: Add WO with a mass ratio of 24:100:2.5 3 -The carbon nanotube composite material, vinyl silicone rubber and dispersant γ-(methacryloyloxy)propyltrimethoxysilane are placed in a mixer and stirred at a speed of 280 r / min to mix evenly, and then refined in an open mill at a refining temperature of 185° C. for 14 min, and then molded in a molding machine to obtain a hydrogen-sensitive color-changing film.

[0065] The multi-walled carbon nanotubes used in the embodiments and comparative examples of the present invention were purchased from Xianfeng Nanomaterial Technology Co., Ltd., with a purity of >98%, a diameter of 4-6 nm, and a length of 0.5-2 μm; the vinyl silicone rubber is high-strength H-110-3 methyl vinyl silicone resin purchased from Zhejiang Hengyecheng Silicone Co., Ltd.; other reagents are commercially available.

[0066] Corresponding tests were performed on the hydrogen-sensitive color-changing films in Examples 1-4 and Comparative Examples 1-2, and the test results are as follows:

[0067] (1) Color change experiment: The hydrogen-sensitive color-changing films in Examples 1-4 and Comparative Examples 1-2 were placed in different test tubes, and 10% hydrogen (90% nitrogen) was introduced at a distance of 10 cm from the sample. The purge flow rate was 10 L / min. During the test, the temperature was 23±2°C and the humidity was 50±10%. Color change occurred during the test, and the substrate turned blue. The color change time was recorded. The test results are shown in Table 1:

[0068] (2) Mechanical property test: Mechanical property test was performed on the hydrogen-sensitive color-changing films in Examples 1-4 and Comparative Examples 1-2, wherein the Shore hardness test was performed according to ASTM D2240-2015 standard, type Shore A; the tensile property test was performed according to GB / T 528-2009 standard, with a tensile rate of 50 mm / min; the test results were recorded respectively; the test results are shown in Table 1:

[0069] Table 1

[0070] Test items Example 1 Example 2 Example 3 Example 4 Comparative Example 1 Comparative Example 2 Color change time (s) 56 50 47 46 68 65 Shore Hardness 69 73 74 74 55 70 Tensile strength (MPa) 11.5 12.3 12.7 12.5 8.4 11.2 Elongation at break (%) 261 272 278 281 219 263

[0071] According to the test results in Table 1, it can be seen that Examples 1-4 have excellent hydrogen response capabilities, fast color change time, high hardness, and good mechanical properties. Carbon nanotubes have a high specific surface area and abundant reaction sites, which can effectively improve the sensitivity and response speed of the composite material. 3 With high electron density and oxygen mobility, it can effectively improve the conductivity and hydrogen sensitivity of the composite material. 3 In the case of V, it exists in the +5 valence state and can replace WO 3 The tungsten atoms in the WO generate holes, which enhance the 3 At the same time, since the radius of vanadium is similar to that of tungsten, it will not destroy WO 3 Crystal structure of V-doped WO 3 With high specific surface area and abundant reaction sites, V-doped WO 3 It can also increase the adsorption capacity of hydrogen and improve the selectivity of hydrogen. The prepared hydrogen-sensitive color-changing film has the characteristics of high sensitivity and short response time. Therefore, the color change time of the hydrogen-sensitive color-changing film corresponding to Example 4 is 46s, the Shore hardness corresponding to Example 3 is 74, the tensile strength is 12.7MPa, and the elongation at break is 278%. In Comparative Example 1, no carbon nanotubes were added, the color change time was prolonged, and the Shore hardness and mechanical properties were greatly reduced; in Comparative Example 2, WO 3 No V atoms are added, the color change time becomes longer, and the Shore hardness and mechanical properties are affected, but the impact is small.

[0072] Although the embodiments of the present invention have been shown and described, it will be understood by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that all equivalent changes and improvements made within the scope of the present invention should still fall within the scope of the patent coverage of the present invention.

Claims

1. A method for preparing a hydrogen-sensitive color-changing film based on nanomaterials, characterized in that: The following steps are involved: Step 1: dissolve sodium tungstate in deionized water, mix well, add sodium metavanadate, adjust the pH to 1.6-2.4 with aqueous hydrochloric acid, add n-propanol, stir and mix, add carbon nanotube dispersion to obtain a mixed solution, transfer the mixed solution to a reactor, and perform a hydrothermal reaction. After the reaction is completed, cool and centrifuge, wash and dry the solid product obtained by centrifugation to obtain a V-doped WO3-carbon nanotube composite material precursor; Wherein, the mass ratio of sodium tungstate, deionized water, sodium metavanadate, n-propanol and carbon nanotube dispersion is 100:130-150:0.2-0.7:1-3:18-30; Step 2: placing the V-doped WO3-carbon nanotube composite material precursor in a muffle furnace, and calcining it in an inert gas atmosphere. After the calcination, cooling it to room temperature in an inert gas atmosphere, grinding and sieving it, to obtain a V-doped WO3-carbon nanotube composite material; Step 3, mixing the V-doped WO3-carbon nanotube composite material, vinyl silicone rubber and dispersant, refining and molding to obtain a hydrogen-sensitive color-changing film based on nanomaterials; Wherein, the mass ratio of the V-doped WO3-carbon nanotube composite material, the vinyl silicone rubber and the dispersant is 18-25:100:1-3.

2. The method for preparing a hydrogen-sensitive color-changing film based on nanomaterials according to claim 1, characterized in that: In the step 1, the temperature of the hydrothermal reaction is 150-180° C., and the time of the hydrothermal reaction is 8-12 hours.

3. The method for preparing a hydrogen-sensitive color-changing film based on nanomaterials according to claim 1, characterized in that: In the step 1, the concentration of the carbon nanotube dispersion is 50 g / L, and the carbon nanotube dispersion is an aqueous solution of carbon nanotubes after acidification; The steps for preparing the acid-treated carbon nanotubes are as follows: The multi-walled carbon nanotubes were added into a 37wt% hydrochloric acid solution in a mass ratio of 1:

5. The mixture was stirred for 1 hour and then ultrasonically dispersed at a temperature of 70-80°C for 3-4 hours. The mixture was filtered and washed with deionized water until neutral. The mixture was vacuum dried at 60°C for 6 hours to obtain the acidified carbon nanotubes.

4. The method for preparing a hydrogen-sensitive color-changing film based on nanomaterials according to claim 1, characterized in that: In the step 2, the calcination temperature is 450-520° C., and the calcination time is 2-3 hours.

5. The method for preparing a hydrogen-sensitive color-changing film based on nanomaterials according to claim 1, characterized in that: In the step 2, the average particle size of the V-doped WO3-carbon nanotube composite material is less than 0.1 μm.

6. The method for preparing a hydrogen-sensitive color-changing film based on nanomaterials according to claim 1, characterized in that: In the step three, the dispersant includes a silane coupling agent.

7. The method for preparing a hydrogen-sensitive color-changing film based on nanomaterials according to claim 1, characterized in that: In the step 3, the rotation speed of the stirring and mixing is 240-300 r / min; the temperature of the refining is 160-200° C., and the refining time is 12-15 min.

8. A hydrogen-sensitive color-changing film based on nanomaterials prepared by the method for preparing a hydrogen-sensitive color-changing film based on nanomaterials as described in any one of claims 1 to 7.

Citation Information

Patent Citations

  • Vanadium-doped crystalline tungsten trioxide electrochromic film and preparation method thereof

    CN114180850A

  • Preparation method of nickel-plated carbon nanotube enhanced PDMS composite film with conductivity and product thereof

    CN112980191A

  • Hydrogen sensor and intelligent monitoring system

    CN115963151A

  • Hydrogen gas sensing film and hydrogen gas sensor

    JP2005331364A